Argumentasi Hukum Aktivis Gender terhadap Penolakan Sanksi Pidana Pelaku Pemerkosaan dalam Rumah Tangga pada Fatwa MUI 2015 - Umam, Misbahul Fuadil (Asian Journal of Law and Humanity, 2025)
This research aims to analyze the views of gender activists regarding MUI Fatwa Number 02/MUNAS-IX/MUI/2015 concerning the rejection of criminal sanctions for perpetrators of domestic rape and to find out the legal arguments from the sources regarding this fatwa. Domestic sexual violence is an important and often overlooked issue in society. This research uses field research methods with an interactive qualitative approach using primary data sources obtained by interview techniques with informants, namely UIN gerder activist K.H Abdurrahman Wahid Pekalongan, and secondary data in the form of research book literature obtained using documentation techniques. The data was analyzed using interactive model qualitative data analysis techniques. The research results concluded that gender activists' views varied regarding the fatwa. Some activists have different views about this fatwa. However, all of them rejected this fatwa on sexual coercion in the household, not sexual violence, because it was deemed not to support the protection of victims and strengthen patriarchal norms. Arguments from gender activists refer to the PKDRT Law which categorizes domestic rape as sexual violence. This research suggests that the fatwa be reviewed and accompanied by case studies to increase public understanding and acceptance and provide appropriate legal solutions for perpetrators of domestic rape.